(untitled) (Docentes 2.0 Journal, 2025)
The Holistic Model proposes a comprehensive approach to education, covering cognitive, affective, and social aspects, seeking to overcome the limitations of traditional approaches that tend to fragment knowledge, promoting life skills, and an equitable and meaningful education, evidenced through the curriculum. The objective was to analyze the implications of the Holistic Model in current education to identify and evaluate how its application can optimize teaching and learning processes. The research was based on the systematic method, naturalistic paradigm, qualitative approach, thematic narrative design, bibliographic documentary type, and cross-section. The compilation and analysis focused on. The databases were Scopus, ScienceDirect, Web of Science, and Google Scholar, applying the PRISMA 2020 method. The articles found were mostly in English from 2020 to 2024. The results identified the challenges that educators face when applying a holistic model as well as the limitations that may arise in different educational contexts, reflecting on the future of the holistic model in education, its emerging trends, as well as understanding how the holistic model can be a valuable tool in current education.